The Phenomenon of Bangladeshi Migrants and Detention Camps in Assam - Sharm, Manu; Alam, Noor (International Journal of Psychosocial Rehabilitation, 2020)
Due to mass migration from Bangladesh to Assam before and after 1971, the local government of Assam has constrained different strategies to filter those who have migrated from Bangladesh to Assam prior to 1971. However, those who migrated after 1971 are considered illegal migrants. Although the filter process through National Registration for Citizenship (NRC) on but on the other side those who got detected as illegal migrants are kept under different detention camps established in Assam. A mass number of individuals confined in those detention camps live a miserable life especially women and children being kept behind the bars with hoodlums as they lack adequate identity proof. This has leaded them in the state of isolation and hindered their right to education and equal opportunities. On the other side people under detention are quite far in performing their socio-economic roles and social participation. However, this has violated the human right norms and universal educational principles UNESCO guidelines. So, it demands urgency to research in this area and to explore the condition of people and process under detention camps of Assam.